Surveilance area detection systems - Wongwutthikrai, Thanyawutthi (Science Technology and Innovation Journal, 2020)
This research has a purpose for, Study of Image Processing Technology, development of detection systems personal from Information of villains and develop a system to detect persons suspected of security with greater precision by image Processing Technology. This system is used processing picture data from Close Circuit Television (CCTV) and use image processing technology for process. Technologies used include: Face detection and Face recognition. This system is used data from CCTV, compare with data of Villain and system alert when the system find the data same a data of Villain.